Covalent Functionalization of Dipole‐Modulating Molecules on Trilayer Graphene: An Avenue for Graphene‐Interfaced Molecular Machines. Issue 22 (28th May 2013) - Nguyen, Phong; Li, Junwen; Sreeprasad, T. S.; Jasuja, Kabeer; Mohanty, Nihar; Ikenberry, Myles; Hohn, Keith; Shenoy, Vivek B.; Berry, Vikas
Abstract The molecular dipole moment plays a significant role in governing important phenomena like molecular interactions, molecular configuration, and charge transfer, which are important in several electronic, electrochemical, and optoelectronic systems. Here, the effect of the change in the dipole moment of a tethered molecule on the carrier properties of (functionalized) trilayer graphene—a stack of three layers of sp2‐hybridized carbon atoms—is demonstrated. It is shown that, due to the high carrier confinement and large quantum capacitance, the trans‐to‐cis isomerisation of 'covalently attached' azobenzene molecules, with a change in dipole moment of 3D, leads to the generation of a high effective gating voltage. Consequently, 6 units of holes are produced per azobenzene molecule (hole density increases by 440 000 holes μm−2). Based on Raman and X‐ray photoelectron spectroscopy data, a model is outlined for outer‐layer, azobenzene‐functionalized trilayer graphene with current modulation in the inner sp2 matrix. Here, 0.097 V are applied by the isomerisation of the functionalized azobenzene. Further, the large measured quantum capacitance of 72.5 μF cm−2 justifies the large Dirac point in the heavily doped system. The mechanism defining the effect of dipole modulation of covalently tethered molecules on graphene will enable future sensors and molecular‐machine interfaces with graphene.